ДЕЯКІ АСПЕКТИ ФАХОВОЇ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ ТЕХНОЛОГІЇ ДО КЕРІВНИЦТВА ТЕХНІЧНОЮ ТВОРЧІСТЮ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2008)
In the article the basic aspects of professional preparation of students are examined to managing technical creation of schoolboys. In particular, an attempt to expose the methodical features of process of teaching of students the decision of technical tasks on the basis of the complex use of knowledges is done.